Transdermal Application of Vitamin D Cream in Individuals with Osteoporosis and Osteopenia - Lekic, Lana; Pavlovic, Bojan (International Journal of Innovative Research in Medical Science, 2024)
It is estimated that over a billion people worldwide have low vitamin D concentrations, justifying the term "pandemic" of vitamin D deficiency, with severe consequences for public health. Vitamin D is a key factor in the prevention and treatment of osteoporosis as it promotes the intestinal absorption of calcium, which is a fundamental prerequisite for normal bone homeostasis. Numerous therapeutic options are available for the prevention and treatment of bone loss, particularly crucial for postmenopausal women and older individuals. The primary measures for preventing bone loss include proper nutrition, physical activity, and adequate intake of vitamin D and calcium. Endocrine societies worldwide provide guidelines recommending calcium and vitamin D intake, typically ranging from 800 to 1200 mg of calcium (from food and supplements) and 800–2000 IU of vitamin D for postmenopausal women with osteoporosis. Osteoporosis leads to a reduction in bone density and quality, exposing women to a higher risk of fractures even with minor injuries or spontaneous falls. The risk of osteoporosis in individuals over 50 is estimated to be about 50% higher in women and 20% higher in men, meaning that women are 2.5 times more likely to be at risk. Vitamin D deficiency also increases the risk of other diseases (comorbidities) such as diabetes, high blood pressure, asthma, and heart disease. Our research focused on the transdermal application of vitamin D, especially in diseases like osteoporosis and osteopenia. The results show that after 2 months of transdermal vitamin D application (twice daily: morning and evening), osteopenia in participants subsided, and the findings returned to normal. Transdermal application of vitamin D is scarcely represented in literature and research, making our study one of the first to address this issue and providing a foundation for further research.